Reconstruction of Floating Market Based Maqashid Sharia Perspective (Case Study in Lok Baintan, Banjar, South Kalimantan) - Ferhad Fasha (Maliki Islamic Economics Journal, 2021)
The aim of this study is to determine: (1) floating market dynamics in Lok Baintan, Banjar Regency, South Kalimantan, (2) floating market building factors in Lok Baintan, Banjar Regency, South Kalimantan, (3) floating market reconstruction in Lok Baintan, Banjar Regency, South Kalimantan Islamic maqashid perspective. This research is a type of field research (field research) using a qualitative approach. There are two types of data sources used, namely primary and secondary data. The results of this study indicate that the dynamics of the Lok Baintan Floating Market consists of four interrelated elements. The factors that influence the construction of the Lok Baintan Floating Market are the development of the Lok Baintan Floating Market, the environmental conditions, the facilities and infrastructure found in the Lok Baintan Floating Market, and government policies related to the Lok Baintan Floating Market. Reconstruction of the Baintan Floating Market in the perspective of maqashid sharia is implemented through the following five things, namely the welfare of the life goals of the local floating market traders, maslahat in consumer behavior, the benefit of the individual is equal to social benefit, the concept of maslahat limits all market activities, and the concept of open maslahat is fulfilled.